Uncertainty in flood routing: diffuse wave models by fuzzy set theory approach - Sales Castro, Maria Patrícia, author; de Lucena, Karyna Oliveira Chaves, author; Vidal, Ticiana Fontoura, author; de Souza, Alice Rocha, author; Chagas, Patricia Freire, author; de Souza, Raimundo Oliveira, author; Colorado State University, publisher (Colorado State University. Libraries, 2018)
Impacts caused by flood routing affect families, economic activities, public and private systems. Impacts and economic losses has increased considerably, because these areas, in general, there is a growing concentration of people and economic activities present in the region. Flood routing is a problem, both developed and developing countries. Many hydrodynamic problems that involve of the propagation flood waves along the length in natural channels are solved by Saint-Venant equations. In most practical applications of flow routing in open channels, inertia terms are negligible, thus the system of Saint-Venant equations is reduced to a parabolic equation, known as the diffusive wave equation. This research aims to apply the fuzzy set theory in diffusive wave models at natural channels, in order to verify the uncertainties related to the hydrodynamic parameters present in these models. Through the implicit finite difference schemes was solved partial differential equations present in Saint-Venant equations. Simulations were carried out for different scenarios in the water body. It was developed a computer program, coded in Fortran. Results allowed establishing some interesting analysis with regard to the behavior of diffusive wave flood routing, it is strong influence of hydraulic parameters, the slope feature and Manning roughness coefficient. Results allowed concluding that the application of the fuzzy set theory in the hydrodynamic systems, it is a viable alternative for determining the uncertainty in flooding and thus be more a support tool in water resources management programs.
Hydrology days 2018
AGU hydrology days 2018
2018 annual AGU hydrology days was held at Colorado State University on March 19 - March 21, 2018.
Keywords: flood routing; fuzzy theory; diffusive wave models